Enhancement of oral production through audiovisual input on a workplace staff. (2016)
One of the main concerns that exists with students from public institutions who are in the English learning process, is that actually they are not able to use the second language to communicate. Students do not reach the levels proposed by the National Bilingualism program (Programa Nacional de Bilinguismo - PNB). To make the necessary changes, new educative tendencies are available for educators, as the ones used throughout this Research project, audiovisual activities and tools for teaching English in working scenarios, but they are still applicable to any educative context.